LOCAL SOLUTION AND BLOW-UP FOR A NONLINEAR BEAM EQUATION OF KIRCHHOFF TYPE WITH DISSIPATIVE TERM - Quispe Méndez, Teófanes (2011)
In present work, we considered a mixed problem for a nonlinear beam equation of Kirchhoff type with dissipative term in a bounded domain. We prove the existence and uniqueness of local solutions with arguments of the fixed point of Banach. Also we obtain the blow-up properties in finite time of solutions and the estimates for the explosion time.